The reconstruction of the past through images: An iconographic1 analysis on the historical imagination usage skills of primary school pupils - (:unkn) unknown (My University, 2009)
The aim of this research is to understand how sixth grade students use their imagination skills in the historical thinking process and, by doing so, how they construct the past. In this respect, .first, an exhibition/museum was visited in the context of social studies during history lessons in a primary school in Kadiköy district in İstanbul.Then, the students were asked to draw their construction of the past in their imagination using historical sources. Nine products/illustrations were selected as a sample according to purposive sampling method. Resulting data were analyzed using the document analysis technique which is one of the qualitative research approaches. As a result of this analysis, although some anachronistic data were found,it was seen that most students have the ability to reconstruct the past appropriate to the historical context using the historical sources, which arc effective in the process of disciplining students'historical imagination. The pupils have the ability to use their former knowledge and experiences during their imagination and thinking processes. It is asserted that the supportive role of the teacher plays a key role in both preparing students to overcome the obstacles that they lace while they are in the process of historical thinking through the usage of historical sources and basing these kinds of skills on a healthy pedagogical ground. © 2009 Eǧitim Danişmanhǧi ve Araşirrmalan İletişim Hizmerleri Tic. Ltd. Şti.
Keywords: Construction of the past; Historical imagination; Historical thinking; Primary pupils